A preliminary study on the synthesis of biogenic derived hydroxyapatite /medicinal plant extracts composite for potential bone tissue engineering applications. (2022) - Mathina, M.; Shinyjoy, E.; Kavitha, L.; Gopi, D.
Abstract: The bone minerals of Hydroxyapatite (Ca10 (PO4 )6 OH2, HAP) are widely utilized in bone repair because of its close similarity to human hard tissues like bone and teeth. HAP has good biocompatible and osteoconductive properties. Naturally derived HAP materials have been widely used in various fields of biomedical applications like filling bones and coating in orthopedics and dental implantation. Hydroxyapatite has considerable mechanical properties, bioactivity, nontoxicity and does not cause any allergic reaction when placed inside the body. To develop an antimicrobial composite for the enhancement of the properties in the tissue engineering applications, HAP powders were prepared by refluxing the cuttlebone (Cb) with diammonium hydrogen phosphate. To the obtained Cb-HAP powders, Carica papaya (Cp) leaf extract was mixed under ultrasonic irradiation techniques to form the Cp induced Cb-HAP composite. Thus, the present work is a preliminary study on the synthesis of Cb-HAP powders and Cp induced Cb-HAP composite for tissue engineering applications. Furthermore, the phase structure and functional group analysis of the prepared composites were investigated through X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR). The morphology of the prepared composite was evaluated by using the Scanning electron microscope (SEM). In addition, the antibacterial activities of the composites were investigated against gram positive and gram-negative pathogens such as E. coli and S. aureus through disc diffusion method. From the obtained results, it can be clear that the Cp induced Cb-HAP exhibited enhanced bacterial inhibition. The observed physicochemical and antibacterial activity suggest that the Cp induced Cb-HAP composite can serve as potential biocomposite for bone tissue engineering applications.